Panel Regression Analysis: Prediksi Ukuran Perusahaan, Modal Kerja, dan Struktur Modal terhadap Return On Assets pada Perusahaan Food and Beverages di Bursa Efek Indonesia - Irawan Irawan; Ari Irawan (Jurnal Riset AKuntansi dan Bisnis, 2022)
. This research approach uses associative quantitative research. The population in this study were 56 companies with a sample of 33 companies that met the sample criteria. Data analysis using Panel Regression was processed with the Eviews 9 application. The test results conclude that the variable firm size and debt to equity ratio partially have a significant effect on return on assets, while working capital turnover partially has no significant effect on return on assets. Simultaneously, company size, working capital turnover, and debt to equity ratio also have a significant effect on the return on assets of manufacturing companies in the consumer goods sector. The contribution given by the variable company size, working capital turnover, and debt to equity ratio to return on assets is 87.07%, while the level of closeness of the variable company size, working capital turnover, and debt to equity ratio to return on assets is very close or very strong.